Analisis Fungsi Manajemen Di Optikal Mandiri Kota Padang - Novalinda , Rina (CV. ITTC INDONESIA, 2021)
The implementation of the management function is not the only element that determines the failure or success of a business, but after all the people who sit in this management have an important role. optical Mandiri Padang city. The type that will be used by researchers in this study is a quantitative descriptive type. Data was collected using a questionnaire, the questionnaire was done by giving written questions to the respondents to be answered by marking (√). Based on the results of the study, it was found that from 30 respondents consisting of 7 employees and 23 Mandiri Optical customers, from the questionnaire questions given to 7 Mandiri Optical employees, there were (100%) who knew management functions in general and (0%) did not know.